A faithful past, a shining future : 75 years of Pentecostal history at North Central University. (Minneapolis, Minn. : North Central University Press, 2006)
Rev. F.J. Lindquist founded North Central Bible Institute in answer to the need for leadership in the expanding Pentecostal movement. This book commemorates North Central University's 75th anniversary with chapters on the institution's history and submissions from North Central alumni. Inside, Men and women share their favorite memories of professors, friendships and life-changing moments from North Central's history.
Keywords: North Central University (Minneapolis, Minn.) -- History; Assemblies of God -- Education -- History; North Central University (Minneapolis, Minn.); Assemblies of God; Education; History